The development of Sn-Cu-Ni lead free composite solder influence by non-metallic reinforcement - Mohd Izrul Izwan Ramli (School of Materials Engineering, 2016)
In this project, a new generation of lead-free (Sn-Cu-Ni) solder alloy was developed to form a composite solder. Five new lead-free composite solders were successfully synthesized using the powder metallurgy method, which consists of mixing, compaction, and sintering process. This research also assisted by a hybrid microwave assisted sintering process, which showed significant advantages in processing compared to conventional sintering method, such as rapid heating rate, shortened sintering time, less energy consumption and less expensive equipment. Five non-metallic reinforcements (Silicon Nitride, Titanium Oxide, Silicon Carbide, Silicon, and Activated Carbon) with various percentages (0, 0.25, 0.5, 0.75, and 1.0 wt. %) were intentionally incorporated into the solder matrix. The microstructure, electrical, thermal, physical properties, and mechanical properties of the composite solders were investigated. Addition of reinforcement particle into a Sn-Cu-Ni solder matrix has led to improvement in thermal performance and mechanical performance. The result also has shown there are no change in the melting temperature and electrical performance. The presence of reinforcement's particles was effective in retarding the interfacial intermetallic layer formation.